Familial autoimmune myasthenia gravis with different pathogenetic antibodies. Issue 9 (September 1988) - Provenzano, C; Arancio, O; Evoli, A; Rocca, B; Bartoccioni, E; de Grandis, D; Tonali, P
Abstract : Two cases of familial myasthenia gravis are reported. One patient is a typical case of autoimmune myasthenia with positive anti acetylcholine receptor antibodies, while in the second patient the impairment of neuromuscular transmission is likely to be due to antibodies directed against determinants other than the acetylcholine receptors.